Towards an approach to decentralized storage and exchange of business process models - Kopp, A. M.; Orlovskyi, D. L. (My University, 2021)
This paper proposes an approach to decentralized storage and exchange of business process models using the blockchain technology and tokenization approach. There was proposed an idea of the Ethereum smart contract that implements the non-fungible token extended with syntactic and semantic properties, which can be used to evaluate quality and estimate value of tokenized business process models.
Keywords: business process modeling; blockchain; tokenization; smart contract